Analisis Siyasah Tanfidziyah Terhadap Implementasi Perda Kabupaten Lampung Barat Nomor 1 Tahun 2017 Tentang Kawasan Tanpa Rokok - Vensy Alaisyahda; Iskandar Syukur; Eti Karini (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The prevalence of smoking behavior in society has become a problem that must be addressed immediately by the government, the dangers of cigarettes are currently not only a problem for adults but also a problem for teenagers, especially those aged 15-18 years, namely children who are still in high school, to overcome this problem, the West Lampung Regency Government has formed a policy on areas that are restricted to not smoking in the environment which is usually called KTR. In this study, the method used is a qualitative research method with the type of field research, the author also uses library research as a support in conducting research, using literature in the library related to the problem to be studied. The findings of the study identified that the Implementation of West Lampung Regency Regional Regulation Number 1 of 2017 concerning Smoke-Free Areas has not been implemented properly, there are no signs or banners for smoke-free areas, and students were found smoking in the school environment, based on Fiqh Siyasah Tafidziyah, the policy regarding the Smoke-Free Area has been in accordance with Islamic law because it was made/determined for the benefit of humanity, but its implementation has not been implemented effectively.